POLITENESS STRATEGIES IN STUDENT`S LANGUAGE OF AS`ADIYAH ERENG ISLAMIC BOARDING SCHOOL, BANTAENG DISTRICT - Anwar; Ikhwan M. Said; Gusnawaty (Bajang Institute, 2022)
Language has the important role in the process of communication in the community. Language politeness is the most appropriate thing to use in communication, because with polite language a person is able to maintain the value and dignity of himself and others. The use of polite language needs to be improved, especially among students who are in the public spotlight that students when interacting prioritize language politeness. In interaction and communication, politeness is one of the important aspects to be raised. Politeness aims to create good relationships and communication in social interaction between speakers and addressees. Both are intended to generate respect for oneself and others, so that the level of politeness will affect the values ​​and perspectives of others towards him. In addition, people will further strengthen the relationship between two. Islamic boarding school is a multilingual society. The diversity of language used by the students is clearly visible when communicating orally. This diversity occurs due to differences in the background of each student. Therefore, researchers are interested in conducting research in Islamic boarding schools. This research is entitled